Go-food User Customer Satisfaction Analysis with Service Quality, Double Order System, and Price - Aurelia Hany Thalita; Laura Sausan Nadirah; Sarinah Sihombing; Nita Rosmala Dewi (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study aims to test and analyze the influence of double order system, service quality, and price on customer satisfaction using GoFood feature in Gojek application in Indonesia. The population of this study is all customer who have used GoFood feature in Gojek application. The sample in this study was 100 respondents. The data used in this study is primary, which is obtained from the results of respondents' answers collected by questionnaires. The sampling technique used is non-probability sampling, namely purposive sampling with descriptive quantitative analysis. Respondents' attitudes were measured by a 5-level likert scale and the data obtained was processed by SPSS (Statistical Product and Service Solution) for windows version 24 analysis. Therefore, this research is to measure the level of customer satisfaction towards double order system, the quality of the products ordered, and the timelines received.